The Empowerment of Persons with Disabilities through Local Potential-Based Entrepreneurship Training in Malang District - Nur Candra Eka Setiawan; Ulfa Rahmawati (Jurnal Pengabdian Pendidikan IPA Kontekstual, 2025)
The KARUNA program aims to improve the economic independence of people with disabilities in the Amanah Bersama Community, Gunungronggo Village, Malang Regency. Activities are carried out through a Community-Based Inclusive Development (CBID) approach with three focus areas: Disability Empowerment, Product Creation, and Marketing Strategy. The results of the activities show an increase in the skills of community members in processing local potential in the form of red guava into high economic value products, an increase in digital marketing capabilities, and the formation of independent businesses. This program has had a positive impact on increasing the confidence, independence, and socio-economic welfare of people with disabilities.